Hybrid Ultra‐Microporous Materials for Selective Xenon Adsorption and Separation. Issue 29 (30th May 2016) - Mohamed, Mona H.; Elsaidi, Sameh K.; Pham, Tony; Forrest, Katherine A.; Schaef, Herbert T.; Hogan, Adam; Wojtas, Lukasz; Xu, Wenqian; Space, Brian; Zaworotko, Michael J.; Thallapally, Praveen K.
Abstract: The demand for Xe/Kr separation continues to grow due to the industrial significance of high‐purity Xe gas. Current separation processes rely on energy intensive cryogenic distillation. Therefore, less energy intensive alternatives, such as physisorptive separation, using porous materials, are required. Herein we show that an underexplored class of porous materials called hybrid ultra‐microporous materials (HUMs) affords new benchmark selectivity for Xe separation from Xe/Kr mixtures. The isostructural materials, CROFOUR‐1‐Ni and CROFOUR‐2‐Ni, are coordination networks that have coordinatively saturated metal centers and two distinct types of micropores, one of which is lined by CrO4 2− (CROFOUR) anions and the other is decorated by the functionalized organic linker. These nets offer unprecedented selectivity towards Xe. Modelling indicates that the selectivity of these nets is tailored by synergy between the pore size and the strong electrostatics afforded by the CrO4 2− anions. Abstract : Try HUMming this : An underexplored class of porous materials called hybrid ultra‐microporous materials (HUMs) affords new benchmark selectivity for Xe separation from Xe/Kr mixtures. They have two distinct types of micropores, one of which is lined by CrO4 2− anions. Modeling studies indicate that the selectivity arises from synergy between the pore size and the strong electrostatics afforded by the CrO4 2− anions.